Charlie's angels [videorecording (DVD)] - McG (Joseph McGinty Nichol); Barrymore, Drew; Barrymore, Drew; Diaz, Cameron; Liu, Lucy, 1968-; Murray, Bill, 1950 September 21-; Rockwell, Sam; Curry, Tim (Columbia Pictures, 2009)
Three women, detectives with a mysterious boss, retrieve stolen voice-ID software, using martial arts, tech skills, and sex appeal.